2021
DOI: 10.15414/jmbfs.3718
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cadmium Toxicity on Leaf Area and Stomatal Characteristics in Faba Bean

Abstract: Although changes in stomatal response to elevated doses of cadmium has already been observed in several plants, few studies have focused on this phenomenon in more detail. The effects of different doses of cadmium Cd2+ (50 and 100 mg.kg-1 soil) on leaf area and stomatal characteristics (number of stomata, number of epidermal cells, stomatal index and size of stomata) of faba bean (Vicia faba L. cultivar Aštar) were studied after 15 days of heavy metal treatment. No visual changes on adaxial or abaxial side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
3
4
0
Order By: Relevance
“…Due to the increasing accumulation of heavy metals and toxic elements in the leaves, we detected several changes in the microanatomical parameters of the leaves of the Arundo lines ( Figure 3 ). Similar to the observations of other authors [ 21 , 35 , 40 , 41 , 60 , 63 , 73 , 74 ] regarding species belonging to the Poaceae family, it was observed that with the toxic element load, the thickness of the epidermis and the extent of the leaf mesophyll decreased.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Due to the increasing accumulation of heavy metals and toxic elements in the leaves, we detected several changes in the microanatomical parameters of the leaves of the Arundo lines ( Figure 3 ). Similar to the observations of other authors [ 21 , 35 , 40 , 41 , 60 , 63 , 73 , 74 ] regarding species belonging to the Poaceae family, it was observed that with the toxic element load, the thickness of the epidermis and the extent of the leaf mesophyll decreased.…”
Section: Resultssupporting
confidence: 90%
“…Wainwright and Woolhouse [ 41 ] also describe a decrease in the size of the stoma apparates alongside an increase in the stomatal density. They established that the size decrease in the subsidiary cells, which is a result of metal toxicity, has an important role in the decrease in the stoma apparates.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies supported this study that the size of the leave stomata was large, and the stomata amount was small, so if the stomata was large, the size of the stomata was small [33], [34], [35]. The plant's response to environmental changes can be seen in changes in the size and number of stomata [36], [37]. The number of epidermal cells was more on the adaxial surface [34].…”
Section: Straight-groovessupporting
confidence: 70%
“…It is known that Cd affects the rate of photosynthesis (i.e., there is a decrease). It has been discussed that such results could be associated with changes in the anatomical structure of the leaf, damage tothe chloroplast structure, a decrease in pigment content, and changes in the light and dark reactions of photosynthesis [ 48 , 49 ]. In this study, a positive effect of MJ on the net photosynthesis rate was observed.…”
Section: Discussionmentioning
confidence: 99%